2000
DOI: 10.1111/j.1708-8208.2000.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurements Comparing the Initial Stability of Five Designs of Dental Implants: A Human Cadaver Study

Abstract: When looking across all bone qualities, the Mark IV implant develops a significantly higher insertion torque than the Standard, Mark II, and Osseotite implant types, and a significantly higher resonance frequency value than the Standard implant, indicating a higher interfacial stiffness at the implant-bone interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
279
4
18

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(312 citation statements)
references
References 10 publications
11
279
4
18
Order By: Relevance
“…Because of its large diameter (4.1 mm), N1 required considerably high torque and force for lateral displacement consistent with previous studies. 22 In addition, both tests proved that tapered miniimplants were more stable than cylindrical ones with either single thread or double thread. 7,11 Because tapered mini-implants are wider in the neck, tighter engagement and greater contact with cortical bone is In this study, SA values were successfully computed using m-CT scans despite the complexity of the design of implants studied.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its large diameter (4.1 mm), N1 required considerably high torque and force for lateral displacement consistent with previous studies. 22 In addition, both tests proved that tapered miniimplants were more stable than cylindrical ones with either single thread or double thread. 7,11 Because tapered mini-implants are wider in the neck, tighter engagement and greater contact with cortical bone is In this study, SA values were successfully computed using m-CT scans despite the complexity of the design of implants studied.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Both tests provide anchorage estimates for immediately loaded MSIs. 7 Peak insertion torque has been shown to be a significant factor in determining the holding power of screw-type implants.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison among different designs of implants was examined in several studies and noticed that conical implants have a higher insertion torque than cylindrical implants 3,9 . However, checking the resonant frequency, Browers et al 1 found higher values for the cylindrical implants compared with the conical, that confirms our results.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of models available in the market or the absence of manufacturer's clarification the effectiveness of the different models leave the surgeon with doubts and raise questions about design features. Implant design should be widely studied by researchers in order to increase the surface area in contact with the bone, consequently the osseointegration, bone anchorage and load distribution [9][10] .…”
Section: Introductionmentioning
confidence: 99%